2017
DOI: 10.1097/md.0000000000007135
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic complications and tip position of transjugular chronic dialysis catheter scheduled into superior vena cava

Abstract: Background:Catheter-related thrombotic complications(TCs) can occur during the long term use of a chronic dialysis catheter (CDC), including fibrin sheath (FS), mural thrombosis (MT), venous thrombosis (VT), and intraluminal clots (IC), which has not been reported with MRI. The aim of our study was to evaluate the determination of catheter tip position (TP) and resolution of TCs in patients with transjugular CDC scheduled into the superior vena cava using high resolution magnetic resonance cholangiopancreatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…2,22 A study that evaluated transjugular catheter tips used in chronic dialysis by means of imaging tests, identified at least one thrombotic complication in 25 of the 38 study participants. 23 Another study conducted in China with 865 patients undergoing dialysis using catheters found that 56.65% of the sample had catheter dysfunction and 38.61% of the patients developed a catheter infection. 24 Problems with central venous catheters can be reduced by correct handling of the device.…”
Section: Discussionmentioning
confidence: 99%
“…2,22 A study that evaluated transjugular catheter tips used in chronic dialysis by means of imaging tests, identified at least one thrombotic complication in 25 of the 38 study participants. 23 Another study conducted in China with 865 patients undergoing dialysis using catheters found that 56.65% of the sample had catheter dysfunction and 38.61% of the patients developed a catheter infection. 24 Problems with central venous catheters can be reduced by correct handling of the device.…”
Section: Discussionmentioning
confidence: 99%